Development of multibody dynamical using MR damper based semi-active bio-inspired chaotic fruit fly and fuzzy logic hybrid suspension control for rail vehicle system. (December 2020) - Bhardawaj, Sono; Sharma, Rakesh Chandmal; Sharma, Sunil Kumar
In this paper, the semi-active suspension in railway vehicles based on the controlled Magnetorheological (MR) fluid dampers is examined, and compared with the semi-active low and semi-active high suspension systems to enhance the running safety, ride quality and ride comfort for a high-speed rail vehicle. Fuzzy logic and chaotic fruit fly control techniques are used as system controllers to determine desired damping forces for front and rear bogie frame with force track-ability of system controllers. A 28 degrees of freedom (DoF) mathematical model of the rail vehicle is formulated using nonlinear vehicle suspension and nonlinear heuristic creep model. The Modified Dahl model is formulated to characterize the behavior of the MR damper. The simulation result is validated using the experimental results. Four different suspension strategies are proposed with MR damper i.e. passive, semi-active low, semi-active high and semi-active intelligent compound controller based on bio-inspired chaotic fruit and fuzzy logic hybrid controller. A comparison indicates that the semi-active controller gives the optimum performance based on frequency and time response analysis for comfort vibration actuation (9.088 to 15.33%), ride quality (14.81–20.73%) and comfort (24.91–27.81%) and it has little influence on derailment quotients, offload factors, as a result, it will not endanger the running safety of rail vehicle.